Pengaruh Struktur Aktiva dan Profitabilitas terhadap Struktur Modal (Studi pada Perusahaan Real Estate dan Property di Bursa Efek Indonesia Tahun 2013) - Putri, Devi Esa; , Imronudin, S.E, M.Si, Ph.D (2016)
Capital structure is a balance between capital and debt used, which means how much capital itself and how much the debt that will be used, so that can produce the optimum capital structure. There are many factors which affect the capital structure of bussiness and this study will examine the effect of assets structure and profitability towards firms' capital structure in real estate and property sector. This study aims to know and examine the effect between assets structure and profitability towards firms' capital structure in real estate and property sector which is enlisted in Indonesian Bursary Effect (BEI) in 2013. The number of sample are 31 firms in real estate and property sector, which use purposive sampling method, means a method of sampling that take the object with specific criteria. The data is obtain from the financial statements and the resume of firms' productivity that published by Indonesian Capital Market Directory (ICMD). The analysis instrument is multiple regression analysis which use SPSS21 software. The hypothesis testing is done by F test, t-test and determination coefficient. The classical assumption that used in this study is normality-tested, auto corerelation-tested, multiple collinear tested, and heteroskedastisitas. The finding of data analysis or regression shows that simultanously structure of assets, profitabilitas, firm size and age of firm affect the capital structure. Partially, the variable that affect capital structure are profitability and the size of the firm where as assets structure and the age of the firm do not affect the capital structure. Keywords: capital structure, structure of assets, profitability, firm size, firm age